Annotated catalogue of beetles (Coleoptera) of the Socotra Archipelago - Hájek, Jiří; Bezděk, Jan (Zootaxa, 2019)
Beetles of the Socotra Archipelago, Yemen, were catalogued. Altogether, 645 morphospecies from 56 families have been recognised from the Archipelago, of which 516 species (one with an additional two subspecies) were identified to the species level. Twenty-four, mostly widely distributed, species are recorded from the Socotra Archipelago for the first time, and three species are newly recorded for the islands Abd el Kuri (1) and Samha (2). Lithocharis socotrana Assing, 2015 (Staphylinidae), described from Socotra, is recorded from continental Yemen for the first time. Five incomplete or incorrect previous records are corrected. A total of 305 (47%) of all recorded species are considered to be endemic to the Socotra Archipelago. A total of 62 (10%) species are widely distributed Afrotropical species, and 35 (5.5%) East African species, often reaching also the Arabian Peninsula; 16 (2.5%) species occur in the eremial zone of Saharo-Arabian (or Saharo-Sindian) region. Only 14 (2%) species were previously known solely from the Arabian Peninsula; 30 (4.5%) species have cosmopolitan (and often anthropogenic) distributions; 28 (4.5%) species are widely distributed in (sub)tropical areas of the Old World; and 26 (4%) species have a predominantly western Palaearctic distribution. At present, 129 (20%) morphospecies remain unidentified; however, we expect that many of them represent as yet undescribed taxa endemic to the Archipelago.